Factors that affect performance measurement system: a critical review / Farhana Zaman and Daeyoung Yoon. - Zaman, Farhana; Yoon, Daeyoung (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2016)
This paper aims to synthesize the research findings on the factors that are related to the uses of performance measures and to realize future research opportunities in this study area. The analysis is based on an in-depth review of several empirical studies published in high quality academic journals in accounting and management. This review paper considers articles published from January 1995 to December 2015. The findings of the paper show that many internal and external factors of an organization, such as size, organizational structure, environmental uncertainty, strategy, market competition, and many other contextual variables, influence the uses of performance measures. Some of these contextual factors are either controllable or not. Therefore, researchers and practitioners need to be conscious of these contingencies before using and analyzing the consequences of performance measures.